Transformation of Public Spaces into Emancipated Spaces by Consumers: a Longitudinal Study on the Belo Horizonte Street Carnival - Fernandes, Lilian Mara Ferreira; Quintão, Ronan Torres (Organizações & Sociedade, 2022)
The aim of this research is to understand how public spaces are transformed into emancipated spaces by consumers. To do so, we used the context of the Belo Horizonte street carnival, a collective moment that occupies the city’s public spaces, in order to question the uses commonly associated with them. A longitudinal investigation was conducted using newspaper articles, the internet, public documents, interviews, and participant observation. As a result, the research presents a theorization on the process of transformation of public spaces into emancipated spaces. In each phase of the process, the contestations regarding the forms of use and consumption of the public space among the social movements of consumers, market players, and the public authority give rise to disputes and tensions that configure the new emancipated space.